(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
An expressive growing in the development of software useful to Psychology is observed in the last years. However, there are few psychologists directly involved in the designing of the programs, especially due to their low ability in computer programming. Some advantages observed in the direct involvement of psychologists-researchers point to the independence to schedule the experiments. The objective of this article is to present a software (ProgRef v3) developed by psychologists to obtain human data from schedules of reinforcement. Other purpose is to contribute to incentive teachers and students in research about the issue, and to incentive more professionals to invest in software program development turned to the research.